TRPV1 Channel: A Noxious Signal Transducer That Affects Mitochondrial Function - Juárez-Contreras, Rebeca (Int J Mol Sci, 2020)
The Transient Receptor Vanilloid 1 (TRPV1) or capsaicin receptor is a nonselective cation channel, which is abundantly expressed in nociceptors. This channel is an important transducer of several noxious stimuli, having a pivotal role in pain development. Several TRPV1 studies have focused on understanding its structure and function, as well as on the identification of compounds that regulate its activity. The intracellular roles of these channels have also been explored, highlighting TRPV1′s actions in the homeostasis of Ca(2+) in organelles such as the mitochondria. These studies have evidenced how the activation of TRPV1 affects mitochondrial functions and how this organelle can regulate TRPV1-mediated nociception. The close relationship between this channel and mitochondria has been determined in neuronal and non-neuronal cells, demonstrating that TRPV1 activation strongly impacts on cell physiology. This review focuses on describing experimental evidence showing that TRPV1 influences mitochondrial function.